Dynamics of the ideal quantum measurement of a spin-1 with a Curie–Weiss magnet - Theodorus Maria Nieuwenhuizen (Frontiers in Quantum Science and Technology)
Quantum measurement is a dynamical process involving an apparatus coupled to a test system. The ideal measurement of the z-component of a spin-12(sz=±12) has been modeled by the Curie–Weiss model for quantum measurement. Recently, the model was generalized to higher spins, and its thermodynamics were solved. Here, the dynamics are considered. To this end, the dynamics for the spin-12 case are cast in general notation. The dynamics of the measurement of the z-component of a spin-1 (sz=0,±1) are solved in detail and evaluated numerically. The energy costs of the measurement, which are macroscopic, are evaluated. The generalization to higher spin is straightforward.